FOREIGN EXPERIENCE’S STUDY OF FINANCIAL AND BUDGET MUNICIPAL INSOLVENCY MANAGEMENT - E. Orlova (Вестник университета, 2017)
On the basis of a research of foreign experience of the organization of the municipal financial relations the main ways of management of the financial and budgetary insolvency of municipal units are defined and systematized. The analysis of the preventive measures directed to improvement of financial bases of local self-government is provided in article, financial aspects of the applied procedures of settlement of arrears in the international practice are characterized. An assessment of a possibility of adaptation of foreign experience when determining ways of overcoming the financial and budgetary insolvency of the Russian municipalities is in conclusion given.